Penggunaan Biometrik dalam Layanan Publik dan Risiko Pelanggaran Privasi - Abid Nurhuda; Nuri Safitri (Sah Publisher, 2026)
The use of biometric technology in public services in Indonesia has expanded significantly in line with the digitalization of government administration and the need for accurate identification systems. The processing of biometric data such as fingerprints, facial features, and iris scans offers benefits in improving efficiency and preventing identity misuse; however, it simultaneously poses serious risks to the protection of citizens’ privacy. The main issues examined concern the legal basis for the use of biometrics in public services, the potential privacy violations that may arise, and the adequacy of the existing legal safeguards. This study adopts a normative juridical approach by examining Indonesian laws and regulations, particularly Law Number 27 of 2022 on Personal Data Protection, as well as regulations governing the provision of public services and electronic systems. The findings indicate that biometric data are classified as specific personal data that require a higher level of protection. Although a legal framework is already in place, the implementation of privacy protection in public service practices still faces challenges, including the risk of data breaches, limitations in oversight mechanisms, and weak fulfillment of data subject rights. Therefore, it is necessary to strengthen technical regulations, enhance state accountability mechanisms, and consistently apply privacy protection principles to ensure that the use of biometrics in public services does not compromise citizens’ right to privacy.